Berberine alleviates oxidative stress in rats with osteoporosis through receptor activator of NF-kB/receptor activator of NF-kB ligand/osteoprotegerin (RANK/RANKL/OPG) pathway - He, Xiao-Feng; Zhang, Long; Zhang, Chun-Hua; Zhao, Con-Ran; Li, Heng; Zhang, Ling-Fei; Tian, Guo-Feng; Guo, Ming-Feng; Dai, Zheng; Sui, Fu-Ge (Biomolecules & biomedicine, 2017)
Previous studies suggested that oxidative stress is related to the onset and development of osteoporosis. Moreover, it was demonstrated that berberine has a protective effect against oxidative stress-induced injuries. In this study, we aimed to investigate the effect and mechanism of action of berberine on rats with induced osteoporosis. Sixty 8-week-old female Wistar rats were randomly divided into the following 6 groups: control saline-treated, osteoporosis saline-treated, 3 osteoporosis berberine-treated groups (Ber 5, 10, and 20 mg/kg/body weight, respectively), and osteoporosis alendronate-treated (ALD) group. Osteoporosis was induced by bilateral ovariectomy. All treatments were performed for 8 weeks. The bone mineral density (BMD), serum alkaline phosphatase (ALP), osteocalcin, calcium, phosphorus, superoxide dismutase (SOD), methylenedioxyamphetamine (MDA), and glutathione peroxidase (GSH-Px) level was determined in the rat femur tissue. The gene and protein expression of osteoprotegerin (OPG) and receptor activator of nuclear factor kappa-B ligand (RANKL) was analyzed by quantitative reverse transcription PCR and Western blot, respectively. The BMD, SOD and GSH⁃Px levels, and the expression of OPG were significantly lower in osteoporosis compared to control group (all p < 0.05). The serum levels of osteocalcin, ALP, and MDA, and the expression of RANKL were significantly higher in osteoporosis compared to control group (all p < 0.05). Berberine, especially the high doses of berberine, effectively increased SOD, GSH⁃Px, and OPG levels as well as decreased serum osteocalcin, ALP, MDA and RANKL levels in berberine-treated osteoporosis groups (all p < 0.05). To conclude, oxidative stress may promote the development of osteoporosis in rats through the RANK/RANKL/OPG pathway. The antioxidative effect of berberine reduces the development of osteoporosis in rats to some extent.